Deskripsi Tingkat Pemahaman Pembuatan Modul Ajar Kurikulum Merdeka pada Calon Guru MI UIN Mahmud Yunus Batusangkar - Fitri Nashito; Meliza Silvi; Mella Puspita; Safrizal Safrizal (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Making teaching modules that are effective and in accordance with the Independent Curriculum is important so that the learning process can run well. This study aims to analyze the level of understanding of semester 6 PGMI teacher candidates in making teaching modules for. The research method used was descriptive research, with a number of 6th semester PGMI teacher candidates as participants. Data were collected by distributing questionnaires and structured interviews to randomly selected participants. Questionnaires and interviews focused on the prospective teacher's understanding of the principles of the Mardeka Curriculum. The results showed that most of the 6th semester PGMI teacher candidates had an adequate understanding of the principles of the Mardeka Curriculum. However, their ability to design teaching modules still needs to be improved. Some of the obstacles faced by prospective teachers in making modules include a lack of knowledge about learning techniques that are in accordance with the Mardeka Curriculum, limited resources, and a lack of training in developing teaching modules. Based on these findings, it is suggested that there is an increase in training and mentoring of 6th semester PGMI teacher candidates in making teaching modules that are in accordance with the Mardeka Curriculum. In addition, it is also necessary to increase the available resources to support the process of making effective teaching modules. Thus, it is hoped that the 6th semester PGMI teacher candidates can develop relevant and high-quality teaching modules in the implementation of the Mardeka Curriculum.